Pelatihan Komputer Untuk Santri Pondok Pesantren Tahfidzul Qur’an Wahidin Halim - Mardi Hardjianto; Lis Suryadi; Dolly Virgian Shaka Yudha Sakti; Gandung Triyono (CV. Multi Kreasi Media, 2025)
This Community Service activity was carried out in collaboration with the Wahidin Halim Tahfidzul Qur'an Islamic Boarding School, an Islamic boarding school located on Jl. H. Gillan RT. 003/RW. 001, Pinang District. Pinang, Tangerang City, Banten 15145. Currently, our partners are struggling to overcome problems arising from the lack of computer training for students. To overcome this problem, we held face-to-face computer training sessions at the ICT Laboratory of Budi Luhur University. The survey evaluation showed that more than 85% of participants felt that the activity was useful, easy to understand, effective, and met their expectations. Therefore, it can be concluded that this activity provides the right solution to partner problems.